CONCEPTS OF BUILDING THE MECHANISM OF MANAGING BUSINESS PROCESSES IN PROVIDING ENTERPRISE ECONOMIC SECURITY - SAMBORSKA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
It is shown that to describe a mechanism of managing business processes, three approaches can be used: the mechanism by purpose, the mechanism in static, and the mechanism in dynamics. Key questions, used models, structural elements of such models, as well as advantages and disadvantages of such approaches are disclosed for each approach.Proposed formal description of the mechanism of managing business processes in ensuring an enterprise economic security is presented as a combination of elements and relationships with defined conditions of non-zero content of certain sets within it. Specifically, the mentioned mechanism is represented in the formal description as a combination of sets of elements and links. It is shown that for each set of designated input signals in the functioning of the mentioned mechanism, there must be at least one reaction. It is shown that each of the designated sets — "Signals", "Reactions", "Elements", and "Connections" for the considered mechanism — must be non-zero. Negative consequences that prevent the functioning of the mechanism are shown in case of zero content of any of these sets.The functionality of the mechanism of managing business processes in ensuring the economic security of the enterprise is presented using the "black box" model, which describes the relationship between input signals and outcomes. It is shown that variation in output results must significantly exceed the variation in input signals.To build a mechanism of managing business processes in ensuring the economic security of the enterprise, it is proposed to use process, functional, situational approaches, and deviation management. For each of these approaches, its use for building the corresponding mechanism is shown.Specific management actions have been identified as the results of functioning of the considered mechanism. These actions include identifying threats and risks, responding to them, monitoring and periodically assessing threats and risks, identifying threats through weak signals, training, stress testing, mitigating the impact of threats, and improving the mechanism itself. For each of these actions, its informational or operational nature has been specified, and the necessary results have been demonstrated.Using the "white box" model, the elements of the mechanism of managing business processes in ensuring the economic security of the enterprise are presented. These elements include áctors, business processes as objects of management, performed functions, influence, used data, decision-making, relationships, and the procedure of comparison.
Keywords: managerial mechanism; business process; management approach; formal condition; “black box”; signal; management action; white box”